Meliolaceae of Kerala, India – XXII - HOSAGOUDAR, V.B. (Indian Phytopathology, 2004)
This paper gives an account of ten new meliolaceous fungi, namely, Asteridiella justiciae, Meliola ardisiicola, M. cannonicola, M. chassaliicola, M. desmodii-velutini, M. erythroxylicola, M. urariae, M. pseudarthriae, M. strychnigena and M. tylophorae-indicae. All these species are described and illustrated in detail.